2021
DOI: 10.3389/fonc.2021.584884
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironmental Competitive Endogenous RNA Network and Immune Cells Act as Robust Prognostic Predictor of Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is malignant hematologic tumors with frequent recurrence and cause high mortality. Its fate is determined by abnormal intracellular competitive endogenous RNA (ceRNA) network and extracellular tumor microenvironment (TME). This study aims to build a ceRNA network related to AML TME to explore new prognostic and therapeutic targets. The RNA expression data of AML were obtained from The Cancer Genome Atlas (TCGA) database. First, we used the ESTIMATE algorithm to calculate the immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…It upregulates after exposure to hydrogen peroxide (oxidative stress), which is consistent with our proposal of its role as a redox-related lncRNA, and may become an indicator of stress responses [ 58 ]. CYP1B1-AS1 is emerging as a powerful prognostic indicator for acute myeloid leukemia (AML), and plays an important part in the intracellular biological process and extracellular microenvironment of AML cells [ 59 ]. Above all, the four lncRNAs in our signature showed potential impacts on multiple types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…It upregulates after exposure to hydrogen peroxide (oxidative stress), which is consistent with our proposal of its role as a redox-related lncRNA, and may become an indicator of stress responses [ 58 ]. CYP1B1-AS1 is emerging as a powerful prognostic indicator for acute myeloid leukemia (AML), and plays an important part in the intracellular biological process and extracellular microenvironment of AML cells [ 59 ]. Above all, the four lncRNAs in our signature showed potential impacts on multiple types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment (TME) dynamically regulates a wide network of interactions between tumor, and stroma cells, in particular immune cells (Arneth, 2019). Although several reports show that long noncoding RNAs (lncRNAs) and circRNAs regulate the TME in solid tumors like prostate cancer, breast cancer and acute myeloid leukemia (Cheng et al, 2021;Jiang et al, 2021), there is no evidence of the interaction among lncRNA-circRNAs-mRNA for modulating the TME.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies applying CIBERSORT to estimate the immune microenvironment for AML all used LM22, which contains the GESs of 22 immunocytes provided by the author as the reference matrix ( Newman et al, 2015 ; Xu et al, 2020 ; Cheng et al, 2021 ; Jia et al, 2021 ). However, the estimates of CTCs might be inaccurate in these studies because of the resemblance between normal immunocytes and malignant leukemic blasts, especially for the myeloid lineages—for example, both Xu et al (2020) and Cheng et al (2021) identified that higher relative proportions of M2 macrophage were associated with a poorer prognosis for AML. Additionally, Xu et al (2020) suggested the marker gene of M2 macrophage CD206, also presenting in immature dendritic cells (DCs) ( Wollenberg et al, 2002 ), as a novel prognostic predictor.…”
Section: Discussionmentioning
confidence: 99%